2021
DOI: 10.2147/dmso.s330741
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Aspartate Aminotransferase/Alanine Aminotransferase Ratio with Diabetic Nephropathy in Patients with Type 2 Diabetes

Abstract: Purpose: To investigate the relationship between aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT) and diabetic nephropathy (DN). Patients and Methods: A total of 402 patients with type 2 diabetes mellitus were divided into three groups, such as normoalbuminuria (n = 196), microalbuminuria (n = 131) and macroalbuminuria (n = 75) groups. Basic information and laboratory results were collected. Serum AST/ALT, tumor necrosis factor-α (TNF-α), interleukin (IL)-2, IL-4, IL-6, IL-10 and interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our findings may implicate enhanced systemic inflammation in FAP patients with a higher AST/ALT ratio. Xu et al have reported that AST/ALT ratio was positively correlated with circulating inflammatory cytokines, such as TNF-α, IL-4, and IL-6, in type 2 diabetes mellitus patients [49]. In the present study, FAP patients with a higher AST/ALT ratio showed a higher count of blood leukocytes (mainly neutrophils and lymphocytes).…”
Section: Discussionsupporting
confidence: 59%
“…Our findings may implicate enhanced systemic inflammation in FAP patients with a higher AST/ALT ratio. Xu et al have reported that AST/ALT ratio was positively correlated with circulating inflammatory cytokines, such as TNF-α, IL-4, and IL-6, in type 2 diabetes mellitus patients [49]. In the present study, FAP patients with a higher AST/ALT ratio showed a higher count of blood leukocytes (mainly neutrophils and lymphocytes).…”
Section: Discussionsupporting
confidence: 59%
“…29,30 In addition, patients with low sALB are also accompanied by high SBP and low levels of ALT, which may also be the reason for the higher incidence of DKD and DR in patients with low sALB. Studies have shown that hypertension and ALT are related to the incidence of DKD and DR. [31][32][33] Therefore, patients with T2DM with lower sALB levels must be screened for DR or DKD. Combined with our subgroup analysis results, DR screening should pay special attention to men aged <65 years, whereas DKD screening should pay attention to people <65 years old.…”
mentioning
confidence: 99%
“…T2DM is a progressive disorder associated with a number of micro- and macrovascular complications. The most common, long-term microvascular consequence of T2DM (diagnosed in ~50% of patients) includes diabetic kidney disease (DKD, formerly diabetic nephropathy, DN), which tends to progress to CKD and eventually to ESRD (in around 30–45% of DKD patients) [ 13 , 62 , 63 ]. The “gold standard” for the early diagnosis of DKD is microalbuminuria, which is, however, not ideal due to limited diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 99%